El Salvador : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for El Salvador. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation discusses that structural reforms, strengthened policy frameworks and the ongoing smooth political transition have laid the foundations for sustained growth in El Salvador. The discussions focused on policies that build on these achievements and address fiscal vulnerabilities, boost long-term growth, and strengthen the governance, anticorruption and Anti-Money Laundering and Combating the Financing of Terrorism frameworks. Continued US dollar appreciation led to a significant decline in inflation and widening of the current account deficit. The authorities agreed that debt would continue to drift upward in the absence of measures, and that weaker-than-expected global growth could have a negative impact on the domestic economy. The authorities emphasized their commitment to guarantee a smooth political transition by sharing information with the new administration and by inviting the Audit Office to oversee the handover process. It is recommended to improve the governance and anticorruption frameworks by increasing the fiscal transparency of the 2020 budget laws, strengthening audit and spending controls, and promptly implementing electronic invoicing.